THE SMALL AND MEDIUM ENTREPRENEURS (SMES) IN THE KURISTAN REGION GOVERNMENT – IRAQ - Sherzad Ahmed Shehab; Mustafa Ahmad Habib; Abdulrezak Nawandy (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The present paper aims to examine the Federal Kurdistan Region’s recent orientation to promote the Small and Medium Entrepreneurs (SMEs), as a part of its strategy after the drop of oil price which is the main revenue of the region, to overcome mass unemployment and to raise the region’s growth. We suggest that this policy is an effort to emulate lessons and past experiences of emerged or developed countries such as Germany and South Korea who after the second world war strongly supported the SMEs community and were able to overcome mass unemployment and to raise the growth. This study uses a statistical data base of the Kurdistan Federal Ministry of Industry and Trade as source of data for analyzing the SMEs status during 2006-2015 in KRG and investigating the possible constraints and pitfalls faced by SMEs community. The study found that SMEs account for approximately (60 percent) of the total job creations in Germany and in South Korea approximately (88 percent) of the total workforce is employed with the SMEs. In the KRG, in contrast, the job creation of SMEs in KRG is comparatively (78.34 percent) in 2015, which is moderate. Caused among others, by the lack of addressing the needs of underdeveloped industrial sphere and pursuing an inadequate promotion policy toward the SMEs and was unable to equip them with the necessary technological knowhow. The study found, however, that the SMEs have a strong potential for effective participation in an acceleration of the wheel of the economy and will prove itself as a major tool for economic